Constitutional amendment in Canada - Gérin-Lajoie, Paul, 1920-2018 (Canadian government series ;, 1950)
On one of the most important and controversial matters in Canada-the drafting of an amending clause to the British North America Act. A forceful, lucid discussion of past amendments, conflicting views, and a possible solution.